Straight Iats in Holly Qura (Journal of the College of Education for Women, 2019)
Thank for Allah lord of worlds and peace be upon his messenger last one of them Muhammadand his followers.The honored thing which the searcher can present to serve the holly quran and all its sciencesin their searching and composing .The straight is the order of Allah is great goal and elite target in this life and every Muslimshould follow and aim to get it and from the mercy of Allah to us he ordered us to follow itand he showed to us how to and to obey him and showed the way to it as was mentioned inthe Quarn ( this is my straight way so you follow it and do not follow other ways ) and the importance of straight he ordered the prophet peace be upon him to catch the right andstraight and warned us from those who follow others away from straight way .And we can consider the straight and its followers to call for Allah and ask him to guide us toit and gather us under the flag of prophet Muhammad the guidance of humanity after Allahhad showed how the Islam is the best and last religion and there is no god only Allah .And we have divided the research into introduction and abstract with meaning of straight andfour sections and with conclusion and results and showed the most important of straight .In the introduction with defined straight in the language and expression and in Sunna with theother meaning with related expressions .- The first section : concluded the order to messenger to be straight .- The second section the order to the prophets to be straight including the stories ofprophets Moses and Haroon peace be upon them .- The third section : the reward of straight in the judgment day .- The fourth section :the straight in the prophet testimony .- The style of the research we have taking the meaning of Iats exited in the holly quranand we used the existed books and we have talked about straight when we mentionedthe iats in the holly quran .Also we have committed to the scientific documentation for what we have mentioned in thepart and page and we have been so careful to the address of the research . and that we lovestraight and we call Allah to make us its people and last call we thank Allah and peace beupon Muhammad and all his followers.